2012
DOI: 10.2140/involve.2012.5.133
|View full text |Cite
|
Sign up to set email alerts
|

Weak Allee effect, grazing, and S-shaped bifurcation curves

Abstract: We study a one-dimensional reaction-diffusion model arising in population dynamics where the growth rate is a weak Allee type. In particular, we consider the effects of grazing on the steady states and discuss the complete evolution of the bifurcation curve of positive solutions as the grazing parameter varies. We obtain our results via the quadrature method and Mathematica computations. We establish that the bifurcation curve is S-shaped for certain ranges of the grazing parameter. We also prove this occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Additionally we recapitulate the subsequent boundary value problem analyzed by Poole et al [2012] for positive solutions: …”
Section: Quadrature Methods For (1-8)mentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally we recapitulate the subsequent boundary value problem analyzed by Poole et al [2012] for positive solutions: …”
Section: Quadrature Methods For (1-8)mentioning
confidence: 99%
“…For the logistic case with Dirichlet boundary conditions, Lee, Sasi, and Shivaji proved the existence of an S-shaped bifurcation curve in one dimension, as well as higher dimensions for a certain range of the grazing parameter [Lee et al 2011]. Regarding the one-dimensional weak Allee effect model with Dirichlet boundary conditions, Poole, Roberson, and Stephenson showed the existence of an S-shaped bifurcation curve, resembling Figure 1, both computationally and analytically for certain parameter ranges [Poole et al 2012]. In particular, our focus is to further examine the structure of positive solutions of (1-7) when the nonlinear boundary conditions (1-4) are satisfied for the range of the parameters where Poole et al [2012] showed the existence of an S-shaped bifurcation curve of positive solutions.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations